Pengenalan literasi minat baca anak dengan didirikan perpustakaan mini di TPA Ar-Rasyid di Dusun Jetis Desa Sidomulyo - Nikmah, Laila Khoerun; Suciani, Tutik; Aufilana, Rahmah Kurnia; Annahdiya, Nabila; Setyaningsih, Wahyu (Nur Science Institute, 2024)
This service aims to define products in community service activities in the form of community empowerment, namely mini-libraries. Mini libraries are essential in increasing interest in reading because mini libraries can also be a bridge to provide information and reading literacy activities for children in Jetis Hamlet, Sidomulyo Village. The service method used is Participatory Action Research. In making a mini library, you must pay attention to several genres and age ratings so that unwanted things do not happen. In addition, the purpose of the product in this community service activity is to provide user education services, for example, tutoring activities so that elementary school-age children can understand some material that they do not understand, and there are fairy tale activities together through a collection of reading books in the mini library. The mini library has many collections of exciting reading books, such as books about religion, general and daily reading books, and so on. With the collection of reading books, elementary school-age children become more happy to visit the mini library. They can also gain knowledge and insight from the collection of reading books to increase their interest in reading through the mini library in children.